Personal Resources on Work Engagement: Study Comparison Based on Length of Service's Nurses Employment in Hospitals - AS, Andi Indahwaty; Irwandy, Irwandy; Arafat, Rosyidah; Saleh, Lalu Muhammad; Ramadany, Sri; Mangilep, Adelia U. Ady; Chalidyanto, Djazuly; Kalsum, Ummu (East Asian Journal of Multidisciplinary Research, 2024)
The current study investigates the comparison between Personal Resources (PR) and Work Engagement (WE) based on Length of Service. This is a quantitative study conducted using a cross-sectional approach. The sample contained 257 employees of three hospitals in South Sulawesi who were selected by simple random sampling and then analyzed using an ANOVA test on SPSS 24. The results of the analysis demonstrated that there was a statistically significant relationship (p < 0.05) between PR and WE based on the employees' length of service within the hospital. Length of Service has an important role in increasing the influence of personal resources and work engagement.